WELFARE IMPACT OF HIGH-NUTRIENT FOODS’ PRICE INCREASE ON INDONESIAN HOUSEHOLDS: IS THERE A ROLE FOR OWN-FARM PRODUCTION? - Rodhiah Umaroh; Evita Hanie Pangaribowo (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/Main Objectives: Significant price increases in food items and uncertainty in the market probably have a severe impact on society, and especially on low-income households. Background Problems: The increases in food prices could have a large impact on the economy and specifically on households. Thus, this study was conducted to investigate what the demand for food, specifically high-nutrient food items, and the impact on welfare are like in Indonesian households when food prices rise. Novelty: There is a great deal of empirical research into the impact of food price changes on household welfare, however studies that have focused on high-nutrient commodities, in particular on self-produced food, are still limited. Many of the previous studies used cross-sectional data for one period but this study used two-wave longitudinal data. Research Methods: Using a large sample of data from the Indonesian Family Life Survey (IFLS), this study employed the quadratic almost ideal demand system (QUAIDS) to identify the demand pattern and applied compensating variation (CV) to understand the impact of soaring food prices on welfare changes. Findings/Results: Overall, the analysis of the impact notes that when prices increase, all household groups would experience welfare losses. The poorest households would experience less of a welfare loss than the richest households, while a larger welfare loss is suffered by households in Java and rural areas. Conclusion: For the low-income households, having their own productive farms could overcome any economic shocks threatening them. Thus, the government should support small-scale farming through such strategic policies as giving them assistance and training in how to manage a small farm.